Ética da responsabilidade ambiental em Hans Jonas e a relevância do diálogo entre a Filosofia, a Biologia e o Direito - Machado, Telma Maria Santos (2014)
This work will focus on the Hans Jonas´ ethics and seek to demonstrate the relevance of, the dialogue between Philosophy, Biology and Law, in full technological era. While recognizing the need for extensive interaction between various areas of knowledge because of the challenges of environmental responsibility that redound to the possibility of having what Jonas calls |authentic human life on the planet|, it became necessary to make an epistemological cut due the for thematic limitation. Mainly in the light of statements contained in the book The imperative of responsibility, the environmental ethics theme will be analyzed from a biological, legal and specially philosophical standpoint. This will be deal with in specific, but not limited chapters, because Jonas´ proposed ethics will guide the analysis of each of them.